2008
DOI: 10.1029/2007jd009760
|View full text |Cite
|
Sign up to set email alerts
|

Role of convection in redistributing formaldehyde to the upper troposphere over North America and the North Atlantic during the summer 2004 INTEX campaign

Abstract: Measurements of CHMultiple tracers were used to arrive at a set of UT CH 2 O background and perturbed air mass periods, and 46% of the TDLAS measurements fell within the latter category. At least 66% to 73% of these elevated UT observations were caused by enhanced production from CH 2 O precursors rather than direct transport of CH 2 O from the boundary layer. This distinction is important, since the effects from the former can last for over a week or more compared to one day or less in the case of convective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 37 publications
13
71
4
Order By: Relevance
“…Thus, the lower than unity values for outflow : inflow ratios for HCHO and H 2 O 2 of 0.54 (0.55 ± 0.09) and 0.59 (0.61 ± 0.08), respectively, are most likely due to partial rain-out of these soluble species. Other studies (Bertram et al, 2007;Fried et al, 2016) derived much lower ratios between outflow and boundary layer inflow, indicating significant entrainment. To estimate the potential role of entrainment for our measurements we apply a two-box model (Cohan et al, 1999) to calculate outflow (OF) mixing ratios from the inflow (IN) and the entrainment (EN) according to OF = x EN + (1 − x)IN.…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the lower than unity values for outflow : inflow ratios for HCHO and H 2 O 2 of 0.54 (0.55 ± 0.09) and 0.59 (0.61 ± 0.08), respectively, are most likely due to partial rain-out of these soluble species. Other studies (Bertram et al, 2007;Fried et al, 2016) derived much lower ratios between outflow and boundary layer inflow, indicating significant entrainment. To estimate the potential role of entrainment for our measurements we apply a two-box model (Cohan et al, 1999) to calculate outflow (OF) mixing ratios from the inflow (IN) and the entrainment (EN) according to OF = x EN + (1 − x)IN.…”
Section: Observationsmentioning
confidence: 99%
“…While insoluble species are efficiently transported to the UT via convection, soluble species are scavenged by cloud and rain droplets, with subsequent removal by precipitation (Wang and Crutzen, 1995;Crutzen and Lawrence, 2000). Nevertheless, recent observations have shown that highly soluble species can also reach the UT via deep convection, most likely due to incomplete removal of these species during pre-cipitation events (Crutzen and Lawrence, 2000;Marie et al, 2000, Barth et al, 2001Yin et al, 2002;Borbon et al, 2012;Bela et al, 2016;Fried et al, 2016). Considerable uncertainty remains with respect to the processes that control the concentrations of soluble species in the outflow of deep convection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade it has emerged that measured HO x in the UT exceeds that predicted by models and that a range of HO x precursors may contribute to this discrepancy. Such precursors include formaldehyde, alkyl peroxides, acetone and isoprene derivatives that are thought to be transported from lower altitudes (Brune, 1998;Collins et al, 1999;Crawford et al, 1999;Colomb et al, 2006;Fried et al, 2008;Jaeglé et al, 2001). These studies have indicated the importance of deep tropical convection and convection from the marine boundary layer on the UT HO x budget.…”
Section: Introductionmentioning
confidence: 99%